Thermal Liquefaction of Olive Tree Pruning Waste Into Bio-Oil in Water and Ethanol With Naoh Catalyst - Öcal,B.; Recepoğlu, Yaşar Kemal; Yüksel Özşen, Aslı; Recepoğlu,Y.K.; Yüksel,A. (Elsevier B.V., 2024)
In this study the effect of catalysts and solvents at varying temperatures on the production of bio-oil from olive tree pruning waste (OPW). The thermal liquefaction process was conducted at 200 °C, 225 °C, and 250 °C for 90 min, employing either water or ethanol as solvents, with alkaline catalysts (0.125 M, 0.25 M, and 0.5 M NaOH) introduced for the first time. Raw material, solid byproducts, and bio-oil samples underwent FTIR analysis for structural changes, TGA for proximate analysis, and GC-MS for bio-oil analysis. Results revealed that NaOH enhanced biomass conversion in water, yet didn't increase bio-oil yield, whereas in ethanol, biomass conversion was relatively lower, but bio-oil yield improved despite the adverse effects of catalyst. The highest biomass conversion (94 %) was achieved at 250 °C with 0.5 M NaOH, but the maximum bio-oil yield (25 %) occurred without a catalyst in water. Conversely, the highest bio-oil yield (55 %) was attained using ethanol without a catalyst at 250 °C. © 2024 Energy Institute
Keywords: Alkaline catalyst; Bio-oil; Lignocellulosic biomass; Olive tree pruning waste; Thermal liquefaction